Multi-sector stakeholder's perceptions of determinants of successful implementation of a pediatric weight management intervention - Persaud, Alicia; Castro, Ines; Simione, Meg; Smith, Justin D.; O'Connor, Giselle; Sharifi, Mona; Perkins, Meghan; Torres, Shioban; Taveras, Elsie M.; Kuhlthau, Karen; Fiechtner, Lauren (Frontiers in Public Health, 2022)
Background Multi-sector stakeholder engagement is essential in the successful implementation, dissemination, and sustainability of pediatric weight management interventions (PWMI), particularly in low-income settings where sustainability relies on external policies and reimbursement. The objective of this study was to engage stakeholders (1) to inform the creation of the intervention with adaptations needed for a successful PWMI in a primary care and community setting and (2) to identify barriers and facilitators to implementation and dissemination. Methods We sought to examine the perspectives of local, state, and national clinic and community stakeholders during the pre-implementation period of a two-arm, randomized trial of a Health Weight Clinic PWMI conducted in two health centers and a modified—Healthy Weight and Your Child PWMI at two local YMCAs that serve a predominantly lower income, Hispanic community. The Consolidated Framework for Implementation Research interview guide served as a template for the study but was modified to fit the PWMIs and the various professional roles. Interviews were transcribed and analyzed using the framework analysis approach and themes were linked to the CFIR domains and constructs. Results Twenty-six stakeholders perceived the following as needed components of a PWMI: a formal curriculum with illustrative examples, a patient- and family-centered program, group visits, and high-quality multidisciplinary personnel. These findings led to the creation of a group visit curriculum, implementation trainings and cross-site collaborative technical assistance. Additionally, creating partnerships between community and clinical organizations, and addressing patient barriers and unmet social needs (i.e., transportation, food) were identified as facilitators to successful implementation. These results led to the creation of community resource guides, connections to community organizations, and screening and referring for unmet social needs. Perceived facilitators of dissemination included proving cost-effectiveness of the PWMI to inform insurance reimbursement for long-term sustainability. Therefore, we collected cost data and engaged with Medicaid officials to discuss reimbursement. Conclusion Findings highlight the importance of engaging multi-sector stakeholders pre-implementation to ensure the components valued are included, ensuring the program minimizes barriers to participation, considering how staff training can improve implementation and how collected outcomes can inform sustainability and dissemination of PWMIs in clinic and community settings.